Effects of Planning on Employees' Performance in Isiolo County Government - Mungania, Agnes; Boru, Hussein (Human Resource and Leadership Journal, 2025)
Purpose: Management by objectives (MBO) is a holistic management planning and control method with a far-reaching impact on an organization's structure, culture, and management approach. It necessitates the governance of the entire management process by utilizing meaningful, specific, and verifiable objectives across various levels of the management hierarchy. In essence, MBO shapes plans, provides guidance, and overseas operations through several mechanisms. This study aimed to investigate effects of planning on Employees' Performance in Isiolo County Government. Grounded in socio-analytic theory this descriptive research involved 260 employees across seven county ministries. Methodology: Data was collected using a questionnaire subjected to pilot testing and reliability analysis (Cronbach's alpha = 0.78). Content validity was established through expert review. Statistical analysis revealed evidence of effective planning practices in Isiolo County. The study shows that employees frequently collaborate with their managers to set goals, and clear objectives are established during the planning process. Managers are actively involved in planning how employees can attain these goals, and desired outcomes are clearly defined. Planning positively impacted overall employee performance. Furthermore, these objectives are effectively communicated to employees, allowing them to focus on achieving them. Findings: The study findings will bridge interdisciplinary knowledge to enhance holistic planning paradigms contributing to good governance and sustainability of organizations. By promoting inclusive and participatory governance through proper planning, this will integrate diverse stakeholder perspectives into policy making. Unique Contribution to Theory, Policy and Practice: The study findings encourage organizations proper planning solutions which are contextually relevant and socially inclusive which will lead to improved employee performance.